Design and construction a portable computerised ultrasonic cloud point measuring system for oil based products - Sudin, Mohammad Radzi; Jaafar, Rosly; Mat Daud, Yaacub; Ayop, Shahrul Kadri (Universiti Teknologi Malaysia, 2003)

(untitled)
A cloud point has excited many researchers to study and improve on its quality and production of palm oil. A computer based of ultrasonic system for determination of cloud point of palm oil sample has being developed. The cloud point can be determined as the temperature at which the significant deviations occur in phase velocity and ultrasonic absorption coefficients curves. Ultrasonic signal was displayed by oscilloscope and any changes in temperature will be detected by semiconductor temperature sensor. A special design of ultrasonic Stepped Test Cell is used in this project that will provide an easy operation on data analyzing. The oscilloscope was connected to the computer through a interface card while the temperature sensor circuit was interfaced through a printer port Ultrasonic data acquisition and analysis, and result display will be computed and controlled by a computer software which is written in Microsoft Visual Basic 6.0 programming language. The cloud point for a few palm oil samples were determined and compared with the result obtained from conventional method.